EFFICACY OF NILOTINIB IN PATIENTS WITH CHRONIC MYELOID LEUKEMIA - Sajid Ali; Tahir Mehmood; kausar Bano; Muhammad Akram et al. (Journal of University Medical & Dental College, 2019)
ABSTRACT: MATERIAL AND METHODS: This study was conducted on 92 diagnosed cases of chronic myeloid leukemia at Department of Oncology, Jinnah Hospital Lahore from August 2016 to January 2017. Patients from either gender, between the ages of 20 to 60 years were included in the study while patients having diabetes and end stage renal disease with glomerular ﬁltration rate less than 15 ml/min were excluded. Nilotinib treatment with the standard dose (300 mg twice daily) was given to patients with chronic phase of chronic myeloid leukemia (CP-CML). Patients were monitored as recommended by the current treatment guidelines. Treatment outcome of CP-CML in terms of eﬃcacy was assessed at the end of 6 months of treatment. OBJECTIVE: To determine the eﬃcacy of nilotinib in patients of chronic myeloid leukemia, chronic phase, in terms of detection of BCR-ABL by FISH method. RESULT: The mean age of the patients was 38.84 ± 11.67 years, with male to female ratio of 1.04:1. The mean PH value of the patients was 17.05 ± 18.53 and eﬃcacy was achieved in 36 (39.13%) patients. CONCLUSION: The eﬃcacy of nilotinib was achieved in signiﬁcant number of CML patients.